Development of tourism in a coastal gmina in terms of objective data and the inhabitants’ opinions: the example of the Gmina of Krokowa - Sokołowski, Dariusz (Turyzm/Tourism, 2014)
Tourism is often seen as an important factor in local development. The good or relatively good financial standing of tourist gminas and their inhabitants is usually emphasised while the positive impact of tourism on the development of infrastructure and other effects generally seen as favourable. What is less often emphasised are the problems associated with the development of tourism. The purpose of this article is to recognise the consequences of tourism development in a gmina of high tourism and recreation value and set them against the opinions of its inhabitants.